Online Prediction of Transient Instability by Wide Area Measurement System - Farhad Namdari; Maryam Nourizadeh; Mahmoodreza Shakarami (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In this paper an online accurate prediction method is proposed to enhance the speed of Transactionient stability assessment. This method is the measurement basis technique resulted from wide area measurement systems (WAMS). In the proposed method, the generators with same dynamic behavior, referred as to coherent generators, are clustered as a same group and they can be considered as an equivalent bus. So the system will be reduced into a small scale system. The admittance matrix parameters of the reduced system can be identified with the least square algorithm. Then the trajectory prediction is performed by real-time simulations. Obtained results from simulations on New England test system show the high noticeable efficiency for performance of the proposed method, capable in predicting of the disturbed trajectory under existence of unknown parameters in grid structure..